Modeling and simulation of 2DEG density and intrinsic capacitances in AlInN/GaN MOSHEMT. (12th July 2017) - Amarnath, G.; Swain, R.; Lenka, T.R.
Abstract: In this paper, an analytical model for intrinsic capacitance is developed by estimating 2‐dimensional electron gas density inside the triangular quantum well in AlInN/GaN metal oxide semiconductor high‐electron mobility transistors by considering gate charge and through self‐consistent solution of Poisson and Schrödinger equations. The charge separation method is applied to develop the intrinsic terminal charges and then the intrinsic capacitances accordingly. In order to validate the developed model, the results are compared with TCAD device simulation results.